Changes in body weight, body composition, and eating attitudes in high school wrestlers - Humenikova Shriver, L.; Mulhollen Betts, N.; Payton, N. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Background: Many wrestlers engage in chronic dieting and rapid "weight cutting" throughout the year to compete in a category below their natural weight. Such weightmanagement practices have a negative influence on their health and nutritional status, so the National Wrestling Coaches Association implemented a new weight-management program for high school wrestlers in 2006. Purpose: The purpose of this study was to determine whether seasonal changes in weight, body fat, and eating attitudes occur among high school wrestlers after the implementation of the new weight-management rule. Methods: Fifteen high school wrestlers participated in the study. Their weight, body composition, and eating attitudes were measured preseason, in-season, and off-season. Body fat was assessed using dual-energy X-ray absorptiometry. Attitudes toward dieting, food, and body weight were assessed using the Eating Attitude Test (EAT). Results: No significant changes in body fat were detected from preseason to off-season. Weight increased from preseason to in-season (p < .05) and off-season (p < .05). Although the EAT score did not change significantly from preseason to offseason, 60% reported "thinking about burning up calories when exercising" during preseason, and only 40% felt that way during the season (p < .05) and 47% during off-season (p < .05). Conclusions: The wrestlers experienced a significant weight gain from preseason to off-season with no significant changes in body fat. Their eating attitudes did not change significantly from preseason to off-season in this study, but further research using a large sample of high school wrestlers is warranted to confirm these findings.